Methyl Alcohol (Methanol) Intoxication - Koca, Tuğçe; Hilal, Ahmet (The Bulletin of Legal Medicine, 2020)
Methanol is a clear, colorless and highly toxic substance obtained from destructive distillation of wood. Methanol, which is generally used as solvent and antifreeze in industrial solvents, paints, varnishes, gasoline mixtures and automobiles, is a type of non-drinking alcohol due to its taste and odor. It can be produced as a by-product during the production of distilled alcoholic beverages. Accidental or suicidal ingestion of methanol can cause intoxication. Methanol often causes oral intoxications. Methanol intoxication occasionally occurs in epidemics. Metabolites of methyl alcohol are toxic. Most of the symptoms of methanol intoxication are associated with metabolic acidosis. Symptoms are usually related to the central nervous system, eyes and gastrointestinal tract and occur after a latent period. It can have serious consequences such as blindness and death. Prognosis is correlated with the degree of metabolic acidosis. The toxic dose of methyl alcohol in human is in a wide range. Hemorrhage and necrosis in the basal ganglia and hemorrhage in the putamen are the findings obtained in radiological examinations and autopsy studies. Methanol levels in the blood of the autopsy cases are quite different. In our country, there has been a significant increase in the number of intoxication cases and deaths as individuals started to produce their own drinks or turned to fake drinks due to the increasing taxes and alcohol prices. In order not to increase the number of intoxication cases and deaths, the government should make the necessary arrangements and take precautions as soon as possible.